Modeling financial instability - Toichiro Asada (Intervention. European Journal of Economics and Economic Policies, 2012)
In this paper, we reconsider Minsky's financial instability hypothesis from the point of view of mathematical macrodynamic modeling. We start from a simple prototype small scale model of private debt and income with fixed prices. This system is similar to the Lotka-Volterra predator-prey system, in which private debt plays the role of predator and income plays the role of prey. Then, we extend the model step by step by introducing variable prices, inflation expectation, public debt and a budget equation of the consolidated government including the central bank. We also study the effect of macroeconomic stabilization policies by means of monetary and fiscal policies.
Keywords: E12; E31; E32; E44; E52; E62; 330; Minsky's financial instability hypothesis; Lotka-Volterra system; private debt; income; public debt; inflation expectation; stabilization policy